Factors Influencing Women Entrepreneur’s Involvement in Tourism and Its Impact on Sustainable Tourism Development in Nepal - Kumari, Anjali (Nepalese Journal of Business, 2025)
This study examines the factor influencing women entrepreneur’s involvement in tourism and its impact on sustainable development in Nepal. Tourism involvement is selected as dependent variable. Similarly, perception of women work, self-efficiency, empowering leadership, psychological empowerment and financial support are selected as independent variables. The study is based on 124 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of selected factor influencing women entrepreneur’s involvement in tourism and its impact on sustainable development in Nepal. The study showed that perception of women work has a positive impact on tourism involvement. It means that better perception of women work lead to an increase in tourism involvement. Similarly, self-efficiency has a positive impact on tourism involvement. It indicates that an increase in self-efficiency leads to an increase in tourism involvement. Moreover, empowering leadership has a positive impact on tourism involvement. It means that an increase in empowering leadership leads to an increase in tourism involvement. Likewise, psychological empowerment has a positive impact on tourism involvement. It shows that the increase in psychological empowerment leads to an increase in tourism involvement. Further, financial support has a positive impact on tourism involvement. It shows that an increase in financial support leads to an increment in tourism involvement in Nepal.